Analisis Etika dalam Struktur Organisasi dan Tata Kelola di SMK Negeri 3 Maumere - Anastasia Yunianti; Maria Faustina Edo; Petrus Kpalet (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyzes the application of ethics in the organizational structure and governance at SMK Negeri 3 Maumere. This research aims to evaluate the impact of implementing ethics on the quality of education, resource management, and student character development. The method used is descriptive qualitative with observation, interviews and documentation. The research results show that SMK Negeri 3 Maumere has implemented ethical principles through a clear organizational structure, transparency in decision making, and commitment to social responsibility. A strict supervision system also increases accountability, while ethics education plays an important role in forming student character. This research concludes that the application of strong ethics in governance contributes to a school's success in achieving its goals, but it is recommended to continually update policies and engage in more effective external oversight.